SYNTHESIS, CHARACTERIZATION, LUMINESCENCE AND DNA BINDING PROPERTIES OF Ln (III)-SCHIFF BASE FAMILY - Vidya Sagar Babu, S.; Krishna Rao, K. S. V.; Ill Lee, Yong (Journal of the Chilean Chemical Society, 2017)
Pentadentate Schiff base ligand(N,N-bis(2-hydroxy-1-naphthylidene) diethylenetriamine) (H2L) that exhibits a N3O2 donor set. Five rare earth complexes lanthanide (III), praseodymium (III), neodymium(III), samarium(III)and europium (III) complexes are synthesized and characterized based on elemental analyses, molar conductance, infrared, ultraviolet, thermo gravimetric, X-ray powder diffraction and mass spectral studies. Molar conductivity data suggests that the complexes are 1:1 electrolytics. Infrared spectral data suggest that the ligand binds through two naptholic oxygen atoms, two azomethine nitrogen atoms and one primary amine. IR studies reveal that the complexes contain both coordinating and ionic nitrate ligands. Thermal decomposition studies indicate the presence of two nitrate ions and two water molecules in the inner coordination sphere. Eu3+ and Sm3+ complexes exhibit luminescence properties. Further, the binding properties of these complexes with calf-thymus DNA have been investigated using absorption spectrophotometry.